Truth and Wisdom - Khan, Steven (Daily Express, 2008)
This article uses a quotation attributed to Chief Seattle (1854) as an example of what curriculum development in the postmodern era must be attentive to, namely, the multiple knowledges and ways of knowing that diverse communities have to offer, and also the ways we must attend carefully to and honour these wisdom traditions
Keywords: Curriculum development; Customs and traditions; Indigenous knowledge